2020
DOI: 10.3892/ol.2020.11563
|View full text |Cite
|
Sign up to set email alerts
|

Role of lymph node dissection in radical cystectomy

Abstract: The number of lymph node dissections (LNDs) is an independent factor influencing the survival time of patients with bladder cancer (BCa) after radical resection (RC). The present study aimed to investigate the association between the number of LNDs and the survival of patients with BCa at different stages and who underwent RC in the United States of America and China. Records from 17,730 American patients with BCa and 158 Chinese patients with BCa were collected from the Surveillance, Epidemiology and End Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…In general, younger patients tend to be healthier, with favorable immune function and nutritional status as well as a lower risk of comorbidities and fewer treatment-related complications. Previous studies have suggested that younger patients prefer to undergo more complete, radical, and combined treatment modalities than older patients (e.g., LND or extensive LND during RC combined with chemotherapy)-a finding also reflected in our study (13)(14)(15)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Indeed, in our study, rates of chemotherapy and the median number of LNE were higher in patients <50 years of age than in patients ≥80 years of age.…”
Section: Subgroup Analysissupporting
confidence: 79%
See 2 more Smart Citations
“…In general, younger patients tend to be healthier, with favorable immune function and nutritional status as well as a lower risk of comorbidities and fewer treatment-related complications. Previous studies have suggested that younger patients prefer to undergo more complete, radical, and combined treatment modalities than older patients (e.g., LND or extensive LND during RC combined with chemotherapy)-a finding also reflected in our study (13)(14)(15)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Indeed, in our study, rates of chemotherapy and the median number of LNE were higher in patients <50 years of age than in patients ≥80 years of age.…”
Section: Subgroup Analysissupporting
confidence: 79%
“…A recent study demonstrated that young patients with MIBC were more likely to have LN metastases than older patients (12). Other studies have also reported a significant association between age and LN status in patients treated with RC (13,14). However, given the limitations of these studies, the precise association between LN+ and patient age at diagnosis of BCa remains to be determined.…”
Section: Original Articlementioning
confidence: 98%
See 1 more Smart Citation
“…According to the TNM stage, BC can be categorized as non-muscular invasive bladder cancer (NMIBC) and muscular invasive bladder cancer (MIBC). Currently, radical cystectomy (RC) with regional pelvic lymphadenectomy (PLND) is the established standard therapy for MIBC and high-risk NMIBC ( 2 , 3 ). However, the survival rate of patients after RC is not satisfactory, with 5-year and 10-year overall survival (OS) rates of 66% and 43%, respectively ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is the most effective treatment for BCa patients, and radical cystectomy (RC), the standard for invasive bladder cancer, has been worldly applied (4). For the accurate prognosis prediction, a series of indicators were introduced to predict the overall survival (OS) and disease-free survival (DFS) of BCa patients after RC, including TNM stage and marital status (5)(6)(7). A simple and effective predictive factor or model for the prognosis of patients assists clinicians to establish the comprehensive individualized treatment of BCa, which will expand the survival time and quality.…”
Section: Introductionmentioning
confidence: 99%